Healthcare resource utilization in Hepatitis C-infected patients completing eight versus twelve weeks of treatment: A retrospective cohort study - Valdez, Katia E.; Javanbakht, Marjan; Keith, Kori; Archer, Roxanne; Deng, John Z.; Marx, Steven E.; Kuznetsova, Arina; Dylla, Douglas E.; Klausner, Jeffrey D. (Frontiers in Gastroenterology, 2022)
Background. The objective of this study was to examine differences in healthcare utilization among patients receiving eight vs. 12-weeks of treatment for infection with the Hepatitis C Virus (HCV). Methods. We conducted a retrospective cohort study among 282 treatment-naïve, HCV-infected patients. Those eligible were uninfected with the Human Immunodeficiency Virus, non-cirrhotic, and treated between 2016 and 2019 as part of an extensive, urban, university-affiliated healthcare system. Electronic medical data were abstracted starting from HCV treatment initiation and up to one year post-initiation or achievement of post-treatment sustained virologic response, whichever occurred first. The primary outcome of interest was healthcare utilization, defined by the number and type of healthcare encounters. Differences in healthcare utilization between those receiving eight vs. 12-weeks of treatment were examined using Student's t-test, Fisher's exact test, Pearson's chi-square test, and the Wilcoxon rank-sum test. Results. A total of 282 eligible patients were analyzed. At baseline, the average age was 59 years (standard deviation=12), and the majority were male (55%) and white/Caucasian (58%). There were no baseline demographic or clinical differences between those completing 8 (n=59) or 12 (n=223) weeks of treatment. While no overall difference in healthcare encounters was observed between those receiving the 8-weeks (median encounters 6; IQR 4-11) and 12-weeks of treatment (median encounters 8; IQR 5-12; P value=0.07), a notable difference was seen in the number of laboratory visits between the groups (median 1 vs. 2; P value=0.04). Conclusions. Our findings indicate modest reductions in healthcare utilization among those receiving shorter treatment regimens for HCV infection, specifically regarding laboratory testing. These findings suggest that shorter treatment regimens may improve treatment expansion in settings that are otherwise too resource-constrained to deliver HCV care successfully.